2020
DOI: 10.1111/papr.12861
|View full text |Cite
|
Sign up to set email alerts
|

Internet‐Based Pain Self‐Management for Veterans: Feasibility and Preliminary Efficacy of the Pain EASE Program

Abstract: Objective To develop and test the feasibility and preliminary efficacy of a cognitive behavioral therapy–based, internet‐delivered self‐management program for chronic low back pain (cLBP) in veterans. Methods Phase I included program development, involving expert panel and participant feedback. Phase II was a single‐arm feasibility and preliminary efficacy study of the Pain e‐health for Activity, Skills, and Education (Pain EASE) program. Feasibility (ie, website use, treatment credibility, satisfaction) was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…It is difficult to summarize findings into meaningful categories given the variety of eHealth-mediated self-management support interventions. Two studies reported good satisfaction, 33 , 34 3 studies reported good acceptability, 35–37 and 2 studies reported that participants with MSDs found the eHealth-mediated self-management support interventions to be beneficial. 38 , 39 …”
Section: Resultsmentioning
confidence: 99%
“…It is difficult to summarize findings into meaningful categories given the variety of eHealth-mediated self-management support interventions. Two studies reported good satisfaction, 33 , 34 3 studies reported good acceptability, 35–37 and 2 studies reported that participants with MSDs found the eHealth-mediated self-management support interventions to be beneficial. 38 , 39 …”
Section: Resultsmentioning
confidence: 99%
“…The majority of the intervention was delivered in a group-format, making it potentially more affordable than individually delivered CBT interventions. Recent CBT-based electronically delivered interventions 40,41 may provide even greater value-for-money, given the potentially lower interventionrelated costs of such approaches. We found few multidisciplinary pain management studies that reported the cost per additional responder as an outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Internet-based CBT programs have been evaluated in other populations with chronic pain [ 71 , 72 ] and have shown promising results. However, these prior programs are largely self-directed, requiring minimal, if any, clinician involvement.…”
Section: Discussionmentioning
confidence: 99%